2017
DOI: 10.3233/rnn-170757
|View full text |Cite
|
Sign up to set email alerts
|

Extended Multiple-Field High-Definition transcranial direct current stimulation (HD-tDCS) is well tolerated and safe in healthy adults

Abstract: Background High definition transcranial direct current stimulation (HD-tDCS) has been administered over single brain regions for small numbers of sessions. Safety, feasibility and tolerability of HD-tDCS over multiple brain regions, multiple daily stimulations and long periods are not established. Objective We studied safety, feasibility and tolerability of daily HD-tDCS over 2–4 brain regions for 20 sessions in healthy adults. Methods Five healthy adults underwent physical and neurological examination, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
0
22
0
1
Order By: Relevance
“…Second, the amount of electrical stimulation that reaches the targeted area is a critical factor in inducing clinical effects. Computational models to estimate cortical electric fields [52] and high-definition tDCS [53] are tools that may help us design more focused tDCS montages. Third, the tDCS dosage could be insufficient in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the amount of electrical stimulation that reaches the targeted area is a critical factor in inducing clinical effects. Computational models to estimate cortical electric fields [52] and high-definition tDCS [53] are tools that may help us design more focused tDCS montages. Third, the tDCS dosage could be insufficient in our study.…”
Section: Discussionmentioning
confidence: 99%
“…; Turski et al . ). For example, HD‐tDCS of the motor cortex has been shown to increase cortical excitability for prolonged periods directly beneath the site of stimulation, as measured by motor evoked potentials (MEPs) using transcranial magnetic stimulation (Kuo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Fortunately, the use of high-definition tDCS (HD-tDCS) partially circumvents this issue through a 4 × 1 electrode montage, with a central electrode surrounded by four electrodes of opposing polarity. Such design provides a more focal and potentially more selective form of neuromodulation (Edwards et al 2013;Kuo et al 2013;Turski et al 2017). For example, HD-tDCS of the motor cortex has been shown to increase cortical excitability for prolonged periods directly beneath the site of stimulation, as measured by motor evoked potentials (MEPs) using transcranial magnetic stimulation (Kuo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These have shown that that tDCS can modulate brain activity, as measured by hemodynamic changes, with effects seen remote from the site of stimulation measured by Blood Oxygenation Level Dependent (BOLD) fMRI (Amadi, Ilie, Johansen‐Berg, & Stagg, ; Antal, Polania, Schmidt‐Samoa, Dechent, & Paulus, ; Polania, Paulus, & Nitsche, ; Sehm, Kipping, Schäfer, Villringer, & Ragert, ; Stagg & Johansen‐berg, ). A previous study using high‐density tDCS (HD‐tDCS), which permits multiple cephalic sites to be simultaneously targeted, also suggests that modulation of whole networks is possible and behaviorally relevant (Turski et al, ). This study provided some evidence that changes in EEG power were correlated with performance on a cognitive battery.…”
Section: Introductionmentioning
confidence: 99%